Supporting Preschool Children’s Executive Functions: Evidence from a Group-Based Play Intervention - UYANIK, GÜLDEN (My University, 2023)
The current study endeavors to assess the impact of the Preschool Executive Functions Intervention Program (PEFIP) on children\"s executive functions. A quasi-experimental design was employed, encompassing both pre-test and post-test assessments within a control group, complemented by follow-up evaluations over a 5-week period. The sample comprises 76 children ranging in age from 54 to 72 months, with 42 in the experimental group and 34 in the control group. Teachers provided assessments of the children\"s executive functions through the Childhood Executive Functions Inventory, while independent researchers employed the Head–Toes–Knees–Shoulders task to evaluate the executive functions of the children. The play-based PEFIP sessions were administered to the experimental group children twice a week for a duration of 10 weeks. Results from the two-way repeated measures analysis of variance (ANOVA) indicated that children in the experimental group exhibited higher levels of teacher-reported working memory, inhibitory control, and performance-based executive function compared to their counterparts in the control group. Furthermore, this improvement in the children persisted in the follow-up assessment conducted 5 weeks after the program\"s completion. These outcomes underscore the efficacy of play-based interventions in bolstering children\"s executive functions.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Gelişim Psikolojisi; Sosyoloji; Eğitim; Social Sciences and Humanities; Psychology; Developmental Psychology; Sociology; Education; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Sosyal Bilimler Genel; PSİKOLOJİ, GELİŞTİRME; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Natural Sciences (SCI); Social Sciences (SOC); PSYCHOLOGY; SOCIAL SCIENCES, GENERAL; PSYCHOLOGY, DEVELOPMENTAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Gelişim ve Eğitim Psikolojisi; Social Sciences & Humanities; Developmental and Educational Psychology; Cognitive flexibility; Executive functions; Inhibitory control; Intervention program; Preschool; Working memory